A Case Report of Spondylitis Due to Salmonella - Yamamoto, Kenji; Mizobe, Hiroyuki; Mitsuyama, Hiromi; Shimizu, Motoharu; Toyoumi, Takashi (Orthopedics & Traumatology, 2000)
Osteomyelitis of the spine caused by Salmonella is rare. The authors describe a case in which the patient had fusion of the L1 to L3 vertebrae, which wereaffected by spondylitis of the Salmonella group O9. A man, sixty-eight years old, had a two-month history of low back pain and gait disturbance without any injury. He was already observed with incomplete paraplegia and bladder disturbance on admission. Laboratory findings suggested mild inflammation. Radiographs of the lumbar spine showed the burst fracture of the L3 vertebra and instability between the L2 and L3 vertebrae. MRI showed the rim enhancment of the abscess in the psoas. We performed anterior intervertebral fusion with iliac bone graft and found Salmonella group O9 from the culture of thegranulation tissue. Six months after, he was able to walk with Lofstrand crutches. Salmonella spondylitis may mimic tuberculous spondylitis both clinically and radiologically. Therefore it is important to discriminate Salmonella spondylitis from other pyogenic or tuberculous spondylitis.